High-strength steel plate and method of manufacturing the same

KR103019588B1Active Publication Date: 2026-09-15JFE STEEL CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
KR1020247021022
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-01-14
Filing Date
2022-12-06
Publication Date
2026-09-15
Estimated Expiration
2042-12-06

Smart Images

  • Figure 112024068112569-PCT00001
    Figure 112024068112569-PCT00001
  • Figure 112024068112569-PCT00002
    Figure 112024068112569-PCT00002
  • Figure 112024068112569-PCT00003
    Figure 112024068112569-PCT00003
Patent Text Reader

Abstract

We provide a high-strength steel plate having a tensile strength of 1320 MPa or higher and excellent ductility, hole expandability, and delayed fracture resistance. The above high-strength steel plate has a specific composition containing Ti, etc., and the amount of diffusible hydrogen in the steel is 0.50 mass ppm or less, tempered martensite and bainite is 70.0 to 95.0%, fresh martensite is 15.0% or less, retained austenite is 5.0 to 15.0%, the average grain size of precipitate A, which is a carbide, nitride, or carbonitride containing at least one element selected from the group consisting of Ti, Nb, and V, is 0.001 to 0.050 μm, the number density NS of precipitate A with a major axis of 0.050 μm or less is 10 particles / μm² or more, and the ratio of the number density NS to the number density NL of precipitate A with a major axis greater than 0.050 μm is 10.0 or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a high-strength steel plate and a method for manufacturing the same. Background Technology

[0002] Recently, from the perspective of global environmental conservation, there is a growing demand to lighten vehicle bodies to improve fuel efficiency.

[0003] At this time, the vehicle body is made lighter while maintaining its strength. For example, it is desired to use high-strength steel plates with a tensile strength (TS) of 1320 MPa or more for the frame parts around the cabin of the vehicle body.

[0004] However, as the strength of steel sheets increases, their ductility tends to decrease. In this case, the formability of the steel sheet becomes insufficient, making it difficult to press-process the steel sheet into complex shapes.

[0005] Therefore, for example, Patent Documents 1 and 2 disclose a technology that achieves both strength and ductility of a steel plate. Prior art literature

[0006] Japanese Published Patent Application No. 2019-2078 Japanese Published Patent Application No. 2011-184756 The problem to be solved

[0007] Conventionally, hot presses are used when processing high-strength steel sheets into parts, but recently, the application of cold presses is being considered in consideration of productivity.

[0008] However, for parts obtained by cold pressing high-strength steel sheets with a tensile strength of 1320 MPa or higher, there is a risk of delayed fracture.

[0009] Delayed fracture is a phenomenon in which, when a stressed component is placed in a hydrogen intrusion environment, hydrogen penetrates into it, causing a decrease in interatomic bonding strength or local deformation, thereby causing microcracks to form and the component to be destroyed as the microcracks propagate.

[0010] For this reason, high-strength steel sheets require good resistance to delayed fracture in addition to sufficient formability (ductility and hole expansion).

[0011] The present invention has been made in consideration of the above points and aims to provide a high-strength steel plate having a tensile strength of 1320 MPa or more, and excellent formability (ductility and hole expansion) and delayed fracture resistance. means of solving the problem

[0012] The inventors, after careful consideration, discovered that the above objective is achieved by adopting the following configuration, and thus completed the present invention.

[0013] That is, the present invention provides the following [1] to [8].

[0014] [1] A composition in mass% containing at least one element selected from the group consisting of C: 0.130 to 0.350%, Si: 0.50 to 2.50%, Mn: 2.00 to 4.00%, P: 0.100% or less, S: 0.0500% or less, Al: 0.010 to 2.000%, N: 0.0100% or less, and Ti: 0.001 to 0.100%, Nb: 0.001 to 0.100% and V: 0.001 to 0.500%, with the remainder being Fe and unavoidable impurities, and a microstructure having a diffusible hydrogen content of 0.50 mass ppm or less in the steel, and in the microstructure, tempered martensite The total area percentage of bainite is 70.0 to 95.0%, the area percentage of fresh martensite is 15.0% or less, the area percentage of retained austenite is 5.0 to 15.0%, and the average grain size of precipitate A, which is a carbide, nitride, or carbonitride containing at least one element selected from the group consisting of Ti, Nb, and V, is 0.001 to 0.050 μm and the major axis is 0.05 μm or less. SNumber density N S 10 pieces / ㎛ 2 That is all, and the above precipitate A S Number density N S Wow, precipitate A, which is the above-mentioned precipitate A with a major axis greater than 0.050 μm. L Number density N L Of N S / N L High-strength steel plate with a value of 10.0 or higher.

[0015] [2] The above composition of the high-strength steel sheet described in [1] further comprises, in mass%, at least one element selected from the group consisting of W: 0.500% or less, B: 0.0100% or less, Ni: 2.000% or less, Co: 2.000% or less, Cr: 1.000% or less, Mo: 1.000% or less, Cu: 1.000% or less, Sn: 0.500% or less, Sb: 0.500% or less, Ta: 0.100% or less, Zr: 0.200% or less, Hf: 0.020% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, and REM: 0.0100% or less.

[0016] [3] High-strength steel sheet described in [1] or [2] having a plating layer on its surface.

[0017] [4] The high-strength steel sheet described in [3] above, in which the plating layer is an alloy plating layer.

[0018] [5] A method for manufacturing a high-strength steel sheet as described in [1] or [2] above, wherein a steel slab having the compositional composition described in [1] or [2] above is heated to 1100°C or higher and hot-rolled at a finishing rolling end temperature of 850 to 950°C to obtain a hot-rolled steel sheet, the hot-rolled steel sheet is coiled at a coiling temperature T of 400 to 700°C, held therein, and then cold-rolled to obtain a cold-rolled steel sheet, and heat treatment is performed on the cold-rolled steel sheet, wherein in the holding period, the sum of the times during which the temperature of the coiled hot-rolled steel sheet is at least the coiling temperature T - 50°C is in unit s and t satisfies the following Equation 1, and in the heat treatment, the cold-rolled steel sheet is maintained at a temperature range T1 of 800 to 950°C for 30 seconds or more, and then 150 to 250 A method for manufacturing a high-strength steel plate, wherein the steel is cooled to a cooling stop temperature T2 of ℃, and then maintained at a temperature range T3 of 250 to 400 ℃ for 30 seconds or more.

[0019] Equation 1 : 0.001 < [1.17×10 -6 ×{t / (T+273.15)}] 1 / 3 < 0.050

[0020] [6] A method for manufacturing a high-strength steel plate as described in [5], wherein, before the above hot rolling, the steel slab is cast and then cooled, and in the cooling of the steel slab, the average cooling rate v1 at 700 to 600 ℃ is 5.0 ℃ / h or higher, and the average cooling rate v2 at 600 to 500 ℃ is 2.5 ℃ / h or higher.

[0021] [7] A method for manufacturing a high-strength steel sheet as described in [5] or [6], wherein, after the heat treatment, a plating treatment is performed on the cold-rolled steel sheet to form a plating layer.

[0022] [8] A method for manufacturing a high-strength steel sheet as described in [7], wherein the plating treatment described above includes an alloying plating treatment that alloys the plating layer. Effects of the invention

[0023] According to the present invention, a high-strength steel plate having a tensile strength of 1320 MPa or more and excellent formability (ductility and hole expansion) and delayed fracture resistance can be provided. Specific details for implementing the invention

[0024] [High-strength steel plate]

[0025] The high-strength steel plate of the present invention has the component composition and microstructure described below, and also satisfies the amount of diffusible hydrogen in the steel described below.

[0026] Hereinafter, "high-strength steel plate" will also be simply referred to as "steel plate."

[0027] The thickness of the steel plate is not particularly limited, but, for example, 0.3 to 3.0 mm, and 0.5 to 2.8 mm is preferred.

[0028] High strength means that the tensile strength (TS) is 1320 MPa or higher.

[0029] The high-strength steel sheet of the present invention has a tensile strength of 1320 MPa or more, and also has excellent formability (ductility and hole expansion) and resistance to delayed fracture. For this reason, the high-strength steel sheet of the present invention has great utility in industrial fields such as automobiles and electrical equipment, and is particularly useful for lightweighting skeletal parts of automobile bodies.

[0030] <Composition>

[0031] The composition of the high-strength steel plate of the present invention (hereinafter also referred to as the “composition of the composition of the present invention for convenience”) will be explained.

[0032] In the component composition of the present invention, “%” means “mass%” unless specifically stated otherwise.

[0033] 《C : 0.130 ∼ 0.350 %》

[0034] C increases the strength of tempered martensite, bainite, and fresh martensite.

[0035] In addition, C improves the stability of the retained austenite, thereby improving the ductility of the steel sheet.

[0036] And, C is a fine precipitate that serves as a hydrogen trap site within tempered martensite and bainite (precipitate A described below). S By precipitating ), the delayed fracture resistance is improved.

[0037] To obtain these effects sufficiently, the amount of C is 0.130% or more, preferably 0.150% or more, more preferably 0.160% or more, and even more preferably 0.170% or more.

[0038] On the other hand, if the C content is excessively high, C distribution to austenite proceeds when reheating during the heat treatment described later, suppressing martensitic or bainite transformations upon cooling after heat treatment, resulting in an excessive area ratio of retained austenite. Furthermore, if the C content is excessively high, the strength of the steel sheet becomes excessively high, increasing the steel's susceptibility to hydrogen embrittlement, making it impossible to obtain sufficient resistance to delayed fracture. Additionally, weldability, which is important when joining automotive parts, deteriorates.

[0039] For this reason, the amount of C is 0.350% or less, preferably 0.330% or less, and more preferably 0.310% or less.

[0040] 《Si : 0.50 ∼ 2.50 %》

[0041] Si suppresses the formation of carbides, thereby suppressing the decrease in hole expandability caused by the difference in hardness between carbides and each microstructure. In addition, stable retained austenite is obtained through Si, ensuring good ductility.

[0042] In order to obtain these effects, the amount of Si is 0.50% or more, preferably 0.55% or more, and more preferably 0.60% or more.

[0043] On the other hand, the excessive content of Si causes the hole expansion capability to deteriorate due to the embrittlement of the steel sheet, making it difficult to obtain the desired formability.

[0044] For this reason, the Si content is 2.50% or less, preferably 2.30% or less, and more preferably 2.00% or less.

[0045] 《Mn : 2.00 ∼ 4.00 %》

[0046] Mn forms a microstructure consisting mainly of tempered martensite and bainite, thereby suppressing the difference in hardness between the structures and improving hole expandability.

[0047] In addition, Mn is an element that contributes to the stabilization of retained austenite and is effective in ensuring good ductility.

[0048] In terms of obtaining these effects, the amount of Mn is 2.00% or more, 2.20% or more is preferable, and 2.50% or more is more preferable.

[0049] On the other hand, if the amount of Mn is excessive, the steel sheet becomes embrittled, the hole expansion ability deteriorates, and it becomes difficult to obtain the desired formability.

[0050] For this reason, the amount of Mn is 4.00% or less, preferably 3.70% or less, and more preferably 3.50% or less.

[0051] 《P : 0.100 % or less》

[0052] P embrittles the steel plate through grain boundary segregation, which has an adverse effect on delayed fracture resistance and weldability. For this reason, the amount of P is 0.100% or less, preferably 0.070% or less, more preferably 0.050% or less, even more preferably 0.030% or less, and particularly preferably 0.010% or less.

[0053] 《S : 0.0500 % or less》

[0054] S segregates at grain boundaries and embrittles the steel sheet during hot working. In addition, S forms sulfides, which adversely affects the resistance to delayed fracture. For this reason, the Si content is 0.0500% or less, preferably 0.0100% or less, and more preferably 0.0050% or less.

[0055] 《Al: 0.010 ~ 2.000%》

[0056] Al reduces inclusions in the steel sheet by acting as a deoxidizer. For this reason, the amount of Al is 0.010% or more, preferably 0.015% or more, and more preferably 0.020% or more.

[0057] On the other hand, if the amount of Al is excessive, the risk of cracking in the steel slab increases when casting the steel slab, thereby reducing manufacturability. For this reason, the amount of Al is 2.000% or less, preferably 1.500% or less, more preferably 1.000% or less, even more preferably 0.500% or less, and particularly preferably 0.100% or less.

[0058] 《N : 0.0100 % or less》

[0059] If coarse nitrides are present in the steel sheet, voids are formed when the steel sheet is sheared, and delayed fracture originating from these voids becomes more likely to occur, thereby deteriorating the steel sheet's resistance to delayed fracture. For this reason, it is desirable for the N content to be as low as possible. Specifically, the N content is 0.0100% or less, preferably 0.0090% or less, and more preferably 0.0080% or less.

[0060] At least one element selected from the group consisting of Ti: 0.001–0.100 %, Nb: 0.001–0.100 %, and V: 0.001–0.500 %

[0061] Ti, Nb, and V contribute to precipitation strengthening, making them effective for increasing the strength of steel sheets. Furthermore, Ti, Nb, and V refine the grain size of prior austenite, or consequently refine tempered martensite and bainite, or fine precipitates that become hydrogen trap sites (precipitate A described below). S By forming ) or making the delayed fracture characteristics better.

[0062] In order to obtain these effects, the amounts of Ti, Nb, and V are each 0.001% or more, preferably 0.003% or more, and more preferably 0.005% or more.

[0063] Meanwhile, if Ti, Nb, and V are excessively abundant, when the steel slab is heated during hot rolling, Ti, Nb, and V remain undissolved, forming coarse precipitates (precipitate A described later). L There are cases where delayed breakdown characteristics deteriorate as ) increases.

[0064] For this reason, the amount of Ti and the amount of Nb are each 0.100% or less, preferably 0.080% or less, and more preferably 0.050% or less.

[0065] The amount of V is 0.500% or less, preferably 0.450% or less, and more preferably 0.400% or less.

[0066] Other Elements

[0067] The composition of the components of the present invention may additionally contain, in mass%, at least one element selected from the group consisting of the elements listed below.

[0068] (W : 0.500 % or less)

[0069] W improves the quenching properties of the steel sheet. In addition, W improves delayed fracture resistance by generating fine carbides containing W that serve as hydrogen trap sites, or by refining tempered martensite and bainite.

[0070] However, if W is excessively high, when heating the steel slab during hot rolling, coarse precipitates such as WN or WS that remain undissolved increase, and the resistance to delayed fracture deteriorates. For this reason, the amount of W is preferably 0.500% or less, more preferably 0.300% or less, and even more preferably 0.150% or less.

[0071] The lower limit of the amount of W is not specifically limited, but from the perspective of obtaining the effect of adding W, for example, 0.010% and 0.050% is preferred.

[0072] (B: 0.0100% or less)

[0073] B is effective for improving quenching properties. In addition, B forms a microstructure consisting mainly of tempered martensite and bainite, thereby preventing a decrease in hole expansion properties.

[0074] However, if B is excessively high, moldability may be reduced. For this reason, the amount of B is preferably 0.0100% or less, more preferably 0.0070% or less, and even more preferably 0.0050% or less.

[0075] The lower limit of the amount of B is not specifically limited, but from the perspective of obtaining the effect of adding B, for example, 0.0005% and 0.0010% is preferred.

[0076] (Ni : 2.000 % or less)

[0077] Ni is an element that stabilizes retained austenite and is effective in ensuring good ductility. In addition, Ni increases the strength of steel through solid solution strengthening.

[0078] Above all, if the amount of Ni is excessively high, the area ratio of fresh martensite becomes excessive, and the pore expandability is reduced. For this reason, the amount of Ni is preferably 2.000% or less, more preferably 1.000% or less, and even more preferably 0.500% or less.

[0079] The lower limit of the Ni amount is not specifically limited, but from the perspective of obtaining the effect of adding Ni, for example, 0.010% and 0.050% is preferred.

[0080] (Co : 2.000 % or less)

[0081] Co is an element effective for improving quenchability and is effective for strengthening steel sheets.

[0082] However, if Co is excessively high, it causes deterioration in moldability. For this reason, the amount of Co is preferably 2.000% or less, more preferably 1.000% or less, and even more preferably 0.500% or less.

[0083] The lower limit of the amount of Co is not specifically limited, but from the perspective of obtaining the effect of adding Co, for example, 0.010% and 0.050% is preferred.

[0084] (Cr : 1.000 % or less)

[0085] Cr improves the balance of strength and ductility.

[0086] However, if the Cr content is excessive, the cementite dissolution rate is delayed when reheating during the heat treatment described later, and relatively coarse carbides with Fe as the main component, such as cementite, remain undissolved, causing the delayed fracture resistance to deteriorate. For this reason, the Cr content is preferably 1.000% or less, more preferably 0.800% or less, and even more preferably 0.500% or less.

[0087] The lower limit of the Cr amount is not specifically limited, but from the perspective of obtaining the effect of adding Cr, for example, 0.030% and 0.050% is preferred.

[0088] (Mo: 1.000 % or less)

[0089] Mo improves the balance of strength and ductility. In addition, Mo improves delayed fracture resistance by producing fine carbides containing Mo that serve as hydrogen trap sites, or by refining tempered martensite and bainite.

[0090] However, if the amount of Mo is excessive, the chemical treatment performance deteriorates significantly. For this reason, the amount of Mo is preferably 1.000% or less, more preferably 0.800% or less, and even more preferably 0.500% or less.

[0091] The lower limit of the amount of Mo is not specifically limited, but from the perspective of obtaining the effect of adding Mo, for example, 0.010% and 0.050% is preferred.

[0092] (Cu : 1.000 % or less)

[0093] Cu is an element effective for strengthening steel. In addition, because Cu inhibits hydrogen from penetrating the steel sheet, it has superior resistance to delayed fracture.

[0094] However, if the amount of Cu is excessive, the area ratio of fresh martensite becomes excessive, and the pore expandability deteriorates. For this reason, the amount of Cu is preferably 1.000% or less, more preferably 0.500% or less, and even more preferably 0.200% or less.

[0095] The lower limit of the amount of Cu is not specifically limited, but from the perspective of obtaining the effect of adding Cu, for example, 0.010% and 0.050% is preferred.

[0096] (Sn: 0.500% or less, Sb: 0.500% or less)

[0097] Sn and Sb suppress decarburization of the surface layer region of the steel plate (a region with a depth of several tens of μm from the surface of the steel plate) caused by nitriding or oxidation of the surface of the steel plate, thereby preventing a decrease in the area ratio of tempered martensite on the surface of the steel plate.

[0098] However, if these elements are excessively abundant, it leads to a decrease in toughness. For this reason, the amount of Sn and the amount of Sb are each preferably 0.500% or less, more preferably 0.100% or less, and even more preferably 0.050% or less.

[0099] The lower limits of the Sn amount and Sb amount are not specifically limited, but from the perspective of obtaining the effect of adding Sn and Sb, for example, 0.001% and 0.003% are preferred, respectively.

[0100] (Ta : 0.100 % or less)

[0101] Ta contributes to high strength by forming alloy carbides or alloy carbonitrides. In addition, Ta is partially dissolved in Nb carbides or Nb carbonitrides to form complex precipitates such as (Nb,Ta) (C,N), thereby significantly suppressing the coarsening of precipitates and stabilizing the contribution to strength by precipitation strengthening.

[0102] However, even if Ta is added in excess, not only are these effects saturated, but costs also increase. For this reason, the amount of Ta is preferably 0.100% or less, more preferably 0.080% or less, and even more preferably 0.070% or less.

[0103] The lower limit of the amount of Ta is not specifically limited, but from the perspective of obtaining the effect of adding Ta, for example, 0.005% and 0.010% is preferred.

[0104] (Zr : 0.200 % or less)

[0105] Zr improves the quenchability of the steel sheet. In addition, Zr improves delayed fracture resistance by generating fine carbides containing Zr that serve as hydrogen trap sites, or by refining tempered martensite and bainite.

[0106] However, if Zr is excessively high, it causes an increase in inclusions, etc., and causes defects on the surface and inside of the steel sheet, thereby deteriorating the delayed fracture resistance. For this reason, the Zr content is preferably 0.200% or less, more preferably 0.150% or less, and even more preferably 0.100% or less.

[0107] The lower limit of the Zr amount is not specifically limited, but from the perspective of obtaining the effect of adding Zr, for example, 0.005% and 0.010% is preferred.

[0108] (Hf : 0.020 % or less)

[0109] Hf affects the distribution state of oxides, making the delayed breakdown characteristics better.

[0110] However, if Hf is excessively high, it degrades the formability of the steel sheet. For this reason, the Hf content is preferably 0.020% or less, more preferably 0.015% or less, and even more preferably 0.010% or less.

[0111] The lower limit of the Hf amount is not specifically limited, but from the perspective of obtaining the effect of adding Hf, for example, 0.001% and 0.003% is preferred.

[0112] (Ca : 0.0100 % or less, Mg : 0.0100 % or less, REM : 0.0100 % or less)

[0113] Ca, Mg, and REM (rare earth metals) spheroidize the shape of sulfides, thereby improving the adverse effect of sulfides on hole expansion.

[0114] However, if these elements are excessively abundant, they cause an increase in inclusions, etc., and cause defects on the surface and inside of the steel sheet, thereby deteriorating the delayed fracture resistance. For this reason, the Ca content, Mg content, and REM content are each preferably 0.0090% or less, more preferably 0.0080% or less, and even more preferably 0.0070% or less.

[0115] The lower limits of the Ca, Mg, and REM amounts are not specifically limited, but from the perspective of obtaining the effect of adding Ca, Mg, and REM, for example, 0.0005% and 0.0010% are preferred, respectively.

[0116] Residue: Fe and inevitable impurities

[0117] The remainder of the composition of the components of the present invention consists of Fe and unavoidable impurities.

[0118] Microtissue

[0119] Next, the microstructure of the high-strength steel plate of the present invention (hereinafter also referred to as the “microstructure of the present invention for convenience”) will be described.

[0120] In order to obtain the effects of the present invention, satisfying only the component composition of the present invention described above is insufficient, and it is necessary to satisfy the microstructure of the present invention described below.

[0121] The area ratio below is the area ratio for the entire microtissue. The area ratio of each tissue is determined by the method described in the [Examples] below.

[0122] Area percentage of total tempered martensite and bainite: 70.0 to 95.0 percent

[0123] Tempered martensite and bainite contribute to tensile strength.

[0124] In addition, using tempered martensite and bainite as the main materials is effective for increasing hole expandability while maintaining high strength.

[0125] To obtain these effects sufficiently, the total area ratio of bainite and tempered martensite is 70.0% or more, preferably 72.0% or more, and more preferably 74.0% or more.

[0126] On the other hand, if there is an excessive amount of tempered martensite and bainite, the amount of retained austenite is insufficient.

[0127] For this reason, the total area ratio of bainite and tempered martensite is 95.0% or less, preferably 93.0% or less, and more preferably 90.0% or less.

[0128] Area ratio of fresh martensite: 15.0% or less

[0129] Fresh martensite creates a large difference in hardness between tempered martensite and bainite, and thus reduces hole expandability during punching due to this difference in hardness. For this reason, it is necessary to avoid having an excess of fresh martensite in the steel sheet.

[0130] Specifically, in terms of obtaining good hole expandability, the area ratio of fresh martensite is 15.0% or less, preferably 14.0% or less, and more preferably 13.0% or less.

[0131] Meanwhile, although the lower limit is not particularly limited, the area ratio of fresh martensite in terms of tensile strength is preferably 1.0% or more, more preferably 3.0% or more, and even more preferably 5.0% or more.

[0132] Area percentage of retained austenite: 5.0 to 15.0 percent

[0133] Retained austenite undergoes a martensitic transformation during processing due to the TRIP (Transformation Induced Plasticity) effect, thereby promoting high strength and simultaneously improving ductility by increasing deformation dispersion ability.

[0134] For this reason, the area percentage of retained austenite is 5.0% or more, preferably 6.0% or more, and more preferably 7.0% or more.

[0135] On the other hand, if there is an excessive amount of retained austenite, voids are likely to form at the interface between the retained austenite and the tempered martensite during processing, and hydrogen embrittlement occurs starting from these voids, which deteriorates the delayed fracture resistance of the steel sheet.

[0136] In addition, hole expandability is reduced because residual austenite undergoes stress-induced martensitic transformation during press forming.

[0137] For this reason, the area percentage of retained austenite is 15.0% or less, preferably 14.0% or less, more preferably 13.0% or less, and even more preferably 12.0% or less.

[0138] Remnant Organization

[0139] Examples of the microstructure excluding tempered martensite, bainite, fresh martensite, and retained austenite (residual microstructure) include ferrite, pearlite, etc. For the reason that it does not impede the effects of the present invention, the area percentage of the residual microstructure in the microstructure of the present invention is preferably 5.0% or less.

[0140] Precipitate A

[0141] Next, precipitate A will be described.

[0142] Precipitate A is a carbide, nitride, or carbonitride containing at least one element selected from the group consisting of Ti, Nb, and V.

[0143] (Average particle size of precipitate A: 0.001 to 0.050 μm)

[0144] If precipitate A is excessively small, the effect of precipitation strengthening is not obtained, and the strength is insufficient.

[0145] For this reason, the average particle size of precipitate A is 0.001 μm or more, preferably 0.005 μm or more, and more preferably 0.010 μm or more.

[0146] On the other hand, if precipitate A is excessively large, it has an adverse effect on the delayed failure characteristics of the shear section.

[0147] For this reason, the average particle size of precipitate A is 0.050 μm or less, preferably 0.040 μm or less, more preferably less than 0.040 μm, even more preferably 0.035 μm or less, particularly preferably 0.030 μm or less, and most preferably 0.020 μm or less.

[0148] The average particle size of precipitate A is determined by the method described in the [Example] below.

[0149] (N S : 10 pieces / ㎛ 2 more)

[0150] Precipitate A S is precipitate A with a major axis of 0.050 μm or less.

[0151] Precipitate A S Number density (number per unit area) N S is 10 pieces / ㎛ 2 That is all.

[0152] Thus, the strength of the steel plate increases due to precipitation strengthening. In addition, fine precipitate A S By acting as a hydrogen trap site, the delayed breakdown characteristics are improved.

[0153] Because it has superior delayed breakdown characteristics, N S is 125 pieces / ㎛ 2 Exceeding 200 particles / ㎛ is desirable. 2 The above is more preferable, with 310 pieces / ㎛ 2 The above is more desirable.

[0154] N S The upper limit of is not specifically limited. However, fine precipitate A S If the absolute amount of increases, the rolling load rises, which may make the manufacture of steel sheets difficult. For this reason, N S is 1,000 pieces / ㎛ 2 The following is preferable, and 800 pieces / ㎛ 2 The following is more desirable.

[0155] (N S / N L : 10.0 or higher)

[0156] Precipitate A L It is precipitate A with a major axis greater than 0.050 μm.

[0157] Precipitate A S Number density N S (Unit: pieces / ㎛) 2 ) and, precipitate A L Number density N L (Unit: pieces / ㎛) 2 The ratio of ) (N S / N L ) is 10.0 or higher. As a result, good delayed breakdown characteristics are obtained. The reason is presumed to be as follows.

[0158] Fine precipitate A S It is thought that it is difficult to accumulate deformation or stress due to the small particle size. In addition, fine precipitate A SSince it is a circular shape, its surface is interpreted as being curved, and it is thought that deformation or stress can easily escape along the curved surface.

[0159] Meanwhile, coarse precipitate A L Silver, fine precipitate A S Compared to, the distance of deformation or stress movement is large, so it is thought that deformation or stress is likely to be retained.

[0160] In particular, coarse precipitate A L It is interpreted that precipitate A, which has a square shape, has a planar surface, and thus is more prone to deformation or stress accumulation. In this case, it is inferred that local deformation or residual stress increases within the shear section. If local deformation or residual stress increases within the shear section, initial cracks are more likely to occur in the shear section, and the delayed fracture resistance of the shear section deteriorates.

[0161] For this reason, coarse precipitate A L By reducing the abundance ratio of, the delayed fracture characteristics of the steel plate can be improved.

[0162] Because it has superior delayed breakdown characteristics, N S / N L A value of 11.0 or higher is preferable, 12.0 or higher is more preferable, greater than 12.1 is even more preferable, 12.2 or higher is particularly preferable, and 13.0 or higher is most preferable.

[0163] N S / N L The upper limit of is not specifically limited, but 100.0 or less is preferred, 80.0 or less is more preferred, 50.0 or less is even more preferred, and 30.0 or less is particularly preferred.

[0164] N L The upper limit of is not specifically limited. However, coarse precipitate A LIt is thought that if the absolute amount of increases, local deformation or residual stress within the shear section rises, making it easier for initial cracks to occur in the shear section. For this reason, N L Silver, 50 particles / ㎛ 2 The following is preferable, and 35 pieces / ㎛ 2 The following is more desirable.

[0165] N S and N L The is obtained by the method described in the [Example] below.

[0166] <Diffusible hydrogen content in steel: 0.50 mass ppm or less>

[0167] From the perspective of securing good delayed fracture resistance characteristics, the diffusible hydrogen content in the steel is 0.50 mass ppm or less, preferably 0.40 mass ppm or less, more preferably 0.30 mass ppm or less, and even more preferably 0.25 mass ppm or less.

[0168] The lower limit of the diffusible hydrogen content in the steel is not specifically limited, but due to production technology constraints, for example, it is 0.01 mass ppm.

[0169] The amount of diffusible hydrogen in the steel is determined by the method described in the [Example] below.

[0170] <Plating layer>

[0171] The high-strength steel sheet of the present invention may have a plating layer on its surface. The plating layer is formed by a plating treatment described later.

[0172] Examples of plating layers include zinc plating layers (Zn plating layers) and Al plating layers, among which zinc plating layers are preferred. The zinc plating layer may contain elements such as Al and Mg. The plating layer may be an alloyed plating layer (alloyed plating layer).

[0173] The plating layer adhesion amount (amount per side) is 20 g / m² from the perspective of plating layer adhesion amount control and corrosion resistance. 2The above is desirable, and 25 g / m² 2 The above is more desirable, and 30 g / m² 2 The above is more desirable.

[0174] Meanwhile, in terms of adhesion, the deposition amount of the plating layer is 120 g / m² 2 The following is preferable, and 100 g / m² 2 The following is more preferable, and 70 g / m² 2 The following is more desirable.

[0175] [Method for manufacturing high-strength steel plates]

[0176] Next, a method for manufacturing a high-strength steel plate according to the present invention (hereinafter also referred to as the "manufacturing method of the present invention" for convenience) will be described.

[0177] Steel Slab

[0178] In the manufacturing method of the present invention, first, a steel slab (steel material) having the component composition of the present invention described above is prepared.

[0179] Steel slabs are cast from molten steel by known methods, such as continuous casting, for example.

[0180] The method for manufacturing molten steel is not particularly limited, and known methods using converters, electric furnaces, etc., may be adopted.

[0181] 《Average cooling rate v1: 5.0 ℃ / h or higher and average cooling rate v2: 2.5 ℃ / h or higher》

[0182] The steel slab may be cooled, for example, by being placed, after casting and before the hot rolling described later is carried out.

[0183] In this cooling, the average cooling rate v1 at 700 to 600 ℃ is preferably 5.0 ℃ / h or higher, more preferably 10.0 ℃ / h or higher, and even more preferably 15.0 ℃ / h or higher.

[0184] The average cooling rate v2 at 600 to 500 ℃ is preferably 2.5 ℃ / h or higher, more preferably 5.0 ℃ / h or higher, and even more preferably 10.0 ℃ / h or higher.

[0185] In steel slabs, during casting, coarse precipitates A L There are cases where this precipitates. When the average cooling rate v1 and average cooling rate v2 satisfy the above ranges, the distribution of precipitates in the steel slab becomes uniform, and the coarse precipitate A precipitated during casting L This makes it easier to remelt when heating the steel slab during the hot rolling process described later. That is, N S / N L The value of is likely to increase.

[0186] The upper limit of the average cooling rate v1 is not specifically limited, for example, 150.0 ℃ / h, and 100.0 ℃ / h is preferred.

[0187] The upper limit of the average cooling rate v2 is not particularly limited, for example, 200.0 ℃ / h or less, and 150.0 ℃ / h is preferred.

[0188] Hot Rolling

[0189] In the manufacturing method of the present invention, a prepared steel slab is hot-rolled under the conditions described below (heating temperature and finish rolling end temperature) to obtain a hot-rolled steel sheet.

[0190] Heating temperature: 1100 ℃ or higher

[0191] During hot rolling, the steel slab is heated.

[0192] If the heating temperature of the steel slab is excessively low, it becomes difficult to sufficiently dissolve at least one element selected from the group consisting of Ti, Nb, and V. Furthermore, because excessive growth of precipitate A occurs, fine precipitate A S Number density N Sga becomes insufficient, or coarse precipitate A L Number density N L This becomes excessive or something. That is, N S / N L The value of is prone to being underestimated. For this reason, the heating temperature of the steel slab is 1100°C or higher, and preferably 1150°C or higher.

[0193] From the perspective of reducing rolling load and from the perspective of smoothing the surface of the steel plate obtained by scaling off surface defects (bubbles, segregation, etc.) of the steel slab, it is desirable that the heating temperature of the steel slab be within the above range.

[0194] The upper limit of the heating temperature of the steel slab is not particularly limited, but if it is excessively high, scale loss increases along with an increase in the amount of oxidation. For this reason, the heating temperature of the steel slab is preferably 1400°C or lower, and more preferably 1350°C or lower.

[0195] Finishing rolling end temperature: 850 ~ 950 ℃

[0196] The steel slab heated to the heating temperature described above undergoes hot rolling, including finish rolling, to become a hot-rolled steel sheet.

[0197] If the finishing rolling end temperature is excessively low, the rolling load increases, resulting in a larger rolling load. In addition, the average grain size of precipitate A becomes excessive, or N S / N L The value of may become too small. In addition, the microstructure of the obtained hot-rolled steel sheet may become coarse, and the microstructure during subsequent heat treatment may also become coarse. In this case, for example, when cooling is stopped, it becomes difficult to reliably obtain mechanically stable fine retained austenite that is difficult to transform into martensite, and as sufficient retained austenite is not obtained, ductility decreases.

[0198] For this reason, the finishing rolling end temperature is 850 ℃ or higher, preferably 855 ℃ or higher, and more preferably 860 ℃ or higher.

[0199] On the other hand, if the finishing rolling end temperature is excessively high, the austenite in the hot-rolled steel sheet becomes coarse, and consequently, the austenite grains in the cold-rolled steel sheet become coarse. In that case, since the diffusion distance of C becomes long, sufficient C enrichment to obtain stable austenite is not induced during the heat treatment described later. As a result, sufficient residual austenite is not obtained in the final microstructure, and ductility decreases.

[0200] In addition, the amount of oxide (scale) generated increases rapidly, and the surface quality tends to deteriorate after the pickling and cold rolling described later.

[0201] In addition, if scale cannot be sufficiently removed by pickling, it has an adverse effect on ductility and hole expansion.

[0202] In addition, the crystal grain size may become excessively coarse, causing surface roughness during press processing.

[0203] For this reason, the finishing rolling end temperature is 950 ℃ or lower, preferably 940 ℃ or lower, and more preferably 930 ℃ or lower.

[0204] <Kwonchwi>

[0205] The hot-rolled steel sheet obtained by hot rolling is wound under the conditions (wound temperature T) described below.

[0206] Winding Temperature T: 400 ~ 700 ℃

[0207] If the winding temperature T is excessively low, precipitate A is not sufficiently formed, resulting in fine precipitate A. S Number density N S ga becomes undervalued, or N S / N L The value of becomes undervalued.

[0208] Furthermore, as the strength of the hot-rolled steel sheet increases, the rolling load during cold rolling increases, or shape defects occur in the cold-rolled steel sheet obtained by cold rolling, resulting in reduced productivity.

[0209] For this reason, the winding temperature T is 400 ℃ or higher, preferably 420 ℃ or higher, and more preferably 430 ℃ or higher.

[0210] On the other hand, if the winding temperature T is excessively high, the growth of precipitate A proceeds, causing the average particle size of precipitate A to become excessive, or N S / N L The value of becomes undervalued.

[0211] For this reason, the winding temperature T is 700 ℃ or lower, preferably 680 ℃ or lower, and more preferably 670 ℃ or lower.

[0212] The coiling temperature T is the cross-sectional temperature of the coiled hot-rolled steel sheet (i.e., coil).

[0213] Stay

[0214] The wound hot-rolled steel sheet (coil) remains until the cold rolling described later is carried out.

[0215] In this residence, when the sum of the times (unit: s) during which the temperature of the coiled hot-rolled steel sheet is at least the coiling temperature T - 50 ℃ is denoted as t (also called "residence time t"), the following Equation 1 is satisfied.

[0216] Equation 1 : 0.001 < [1.17×10 -6 ×{t / (T+273.15)}] 1 / 3 < 0.050

[0217] Hereinafter, for convenience, "[1.17×10" in the above Equation 1 -6 ×{t / (T+273.15)}] 1 / 3 」 is written as 「X」.

[0218] If X in Equation 1 above falls below the lower limit, the coil's retention is stopped in a state where sufficient nucleation does not occur or nucleation growth is insufficient, resulting in an undersized average particle size of precipitate A, or N S / N L The value of becomes undervalued.

[0219] Meanwhile, if X in the above Equation 1 exceeds the upper limit, precipitate A undergoes excessive Ostwald growth due to the diffusion of Ti, Nb or V, and C or N, causing the average particle size of precipitate A to become excessive, or N S / N L The value of becomes undervalued.

[0220] Methods for controlling the thermal history of a wound hot-rolled steel sheet (coil) are not particularly limited, and examples include covering the coil, applying hot air and / or cold air to the coil, etc.

[0221] The temperature of the wound hot-rolled steel sheet (coil) is the temperature of the coil surface measured using a radiation thermometer when there is no cover, and the temperature inside the cover measured using a thermocouple when there is a cover.

[0222] For coils that have been held under conditions satisfying Equation 1 above, pickling may be performed as needed before the cold rolling described later. The pickling method may follow conventional methods. Skin pass rolling may be performed to correct the shape and improve pickling performance.

[0223] Cold Rolling

[0224] The coiled hot-rolled steel sheet is kept under conditions satisfying the above Equation 1, and if necessary, is pickled and then cold-rolled to become a cold-rolled steel sheet.

[0225] The reduction rate in cold rolling is preferably 25% or more, and more preferably 30% or more.

[0226] Meanwhile, excessive reduction leads to an excessive rolling weight, causing an increase in the load on the mill used for cold rolling. For this reason, a reduction rate of 75% or less is desirable, and 70% or less is more desirable.

[0227] Heat Treatment

[0228] The cold-rolled steel sheet obtained by cold rolling is subjected to heat treatment under the conditions described below.

[0229] In summary, a cold-rolled steel sheet is held (heated) at temperature range T1, then cooled to a cooling stop temperature T2, and then held (reheated) at temperature range T3.

[0230] Temperature Range T1 : 800 ∼ 950 ℃

[0231] When the temperature of the temperature range T1 is excessively low, the two-phase region is maintained, so the total area ratio of tempered martensite and bainite in the final microstructure is reduced.

[0232] For this reason, the temperature of the temperature range T1 is 800 ℃ or higher, preferably 830 ℃ or higher, and more preferably 850 ℃ or higher.

[0233] Meanwhile, if the temperature in temperature range T1 is excessively high, precipitate A formed during hot rolling coarsens, causing the average grain size of precipitate A to become excessive, or N S / N L The value of becomes undervalued.

[0234] For this reason, the temperature of the temperature range T1 is 950 ℃ or lower, preferably 940 ℃ or lower, and more preferably 930 ℃ or lower.

[0235] 《Hold time at temperature range T1: 30 seconds or more》

[0236] If the holding time in the temperature range T1 is excessively short, sufficient recrystallization is not carried out. In addition, the formation of austenite becomes insufficient, and the area percentage of retained austenite becomes too low.

[0237] For this reason, the holding time in temperature range T1 is 30 seconds or more, preferably 65 seconds or more, and more preferably 100 seconds or more.

[0238] The upper limit of the holding time in temperature range T1 is not specifically limited, for example, 800 seconds, 500 seconds is preferred, and 200 seconds is more preferred.

[0239] Cooling Stop Temperature T2: 150 ~ 250 ℃

[0240] If the cooling stop temperature T2 is excessively low, the amount of untransformed austenite remaining when cooling is stopped becomes small, and ultimately the area percentage of the retained austenite becomes insufficient.

[0241] For this reason, the cooling stop temperature T2 is 150 ℃ or higher, preferably 160 ℃ or higher, and more preferably 170 ℃ or higher.

[0242] Meanwhile, if the cooling stop temperature T2 is excessively high, a large amount of residual austenite remains when cooling is stopped, and ultimately the area ratio of residual austenite becomes excessive.

[0243] For this reason, the cooling stop temperature T2 is 250 ℃ or lower, preferably 240 ℃ or lower, and more preferably 230 ℃ or lower.

[0244] Temperature Range T3: 250–400 ℃

[0245] If the temperature in temperature range T3 is excessively low, C is not sufficiently enriched in the untransformed austenite, and the area percentage of the retained austenite becomes insufficient.

[0246] For this reason, the temperature of temperature range T3 is 250 ℃ or higher, preferably 260 ℃ or higher, and more preferably 270 ℃ or higher.

[0247] On the other hand, if the temperature in the temperature range T3 is excessively high, the decomposition of the untransformed austenite proceeds excessively, and the area ratio of the retained austenite becomes insufficient, so the ductility decreases.

[0248] For this reason, the temperature of temperature range T3 is 400 ℃ or lower, preferably 380 ℃ or lower, and more preferably 360 ℃ or lower.

[0249] 《Hold time at temperature range T3: 30 seconds or more》

[0250] If the holding time in the temperature range T3 is excessively short, the area percentage of fresh martensite in the final microstructure becomes excessive, or the area percentage of retained austenite becomes insufficient due to insufficient C enrichment into retained austenite.

[0251] For this reason, the holding time in temperature range T3 is 30 seconds or more, preferably 100 seconds or more, and more preferably 180 seconds or more.

[0252] The upper limit of the holding time in temperature range T3 is not specifically limited, for example, 800 seconds, 500 seconds is preferred, and 300 seconds is more preferred.

[0253] <Plating Treatment>

[0254] For the cold-rolled steel sheet subjected to the heat treatment described above, a plating treatment to form a plating layer may be performed. Examples of plating treatments include hot-dip galvanizing. In this case, a zinc plating layer is formed as the plating layer.

[0255] When performing hot-dip galvanizing treatment, for example, a cold-rolled steel sheet that has undergone the heat treatment described above is immersed in a hot-dip galvanizing bath at 440 to 500°C. After immersion, the amount of the plating layer adhered is adjusted by gas wiping, etc.

[0256] The molten zinc plating bath may contain elements such as Al, Mg, and Si, and may also contain elements such as Pb, Sb, Fe, Mg, Mn, Ni, Ca, Ti, V, Cr, Co, and Sn. The amount of Al in the molten zinc plating bath is preferably 0.08 to 0.30%.

[0257] The plating treatment may include an alloying treatment that alloys the formed plating layer.

[0258] When performing an alloying treatment after hot-dip galvanizing, the zinc plating layer is alloyed at a temperature of 450 to 600°C (alloying temperature). If the alloying temperature is excessively high, the untransformed austenite transforms into pearlite, and the area percentage of the retained austenite becomes insufficient.

[0259] The Fe concentration of the alloyed zinc plating layer is preferably 8 to 17 mass%.

[0260] In the case where plating treatment is performed, the cold-rolled steel sheet subjected to heat treatment and plating treatment corresponds to the high-strength steel sheet of the present invention.

[0261] Meanwhile, in cases where plating treatment is not performed, a heat-treated cold-rolled steel sheet corresponds to the high-strength steel sheet of the present invention.

[0262] Examples

[0263] The present invention will be specifically described below with reference to examples. However, the present invention is not limited to the examples described below.

[0264] Manufacture of steel plates

[0265] Molten steel having the composition shown in Table 1 below, with the remainder being Fe and unavoidable impurities, was produced in a converter, and a steel slab was obtained by a continuous casting method.

[0266] The obtained steel slab was cooled under the conditions shown in Table 2 below.

[0267] Next, the cooled steel slab was subjected to hot rolling, coiling, dwelling, cold rolling, and heat treatment under the conditions shown in Table 2 below to obtain a cold-rolled steel sheet (CR) with a thickness of 1.4 mm. The reduction rate for cold rolling was set to 50%.

[0268] For several cold-rolled steel sheets, a galvanized layer was formed on both sides by performing a hot-dip galvanizing treatment to obtain hot-dip galvanized steel sheets (GI). The amount of the galvanized layer (amount per side) was 45 g / m² 2 ...did so.

[0269] In addition, for several hot-dip galvanized steel sheets (GI), the zinc plating layer formed by performing an alloying treatment was alloyed to obtain an alloyed hot-dip galvanized steel sheet (GA). In the alloying treatment, the Fe concentration of the alloyed zinc plating layer was adjusted to be within the range of 9 to 12 mass%.

[0270] For the hot-dip galvanized steel sheet (GI), a hot-dip galvanizing bath with an Al content of 0.19 mass% was used. For the hot-dip galvanized steel sheet (GA), a hot-dip galvanizing bath with an Al content of 0.14 mass% was used. The bath temperature was set to 465 ℃ for all.

[0271] Hereinafter, for convenience, cold-rolled steel sheets (CR), hot-dip galvanized steel sheets (GI), and alloyed hot-dip galvanized steel sheets (GA) are all simply referred to as "steel sheets."

[0272] In the “Type” column of Table 2 below, “CR,” “GI,” and “GA” are indicated depending on the obtained steel plate.

[0273] Observation of Micro-tissues

[0274] The obtained steel plate was polished so that the cross-section (L cross-section) at the 1 / 4 position of the plate thickness parallel to the rolling direction (a position corresponding to 1 / 4 of the plate thickness in the depth direction from the surface of the steel plate) became the observation surface, and an observation sample was prepared.

[0275] Using the prepared observation samples, the microstructure was observed as follows, and the area ratio of each tissue was calculated. The results are shown in Table 3 below.

[0276] In Table 3 below, tempered martensite is denoted as “TM”, bainite as “B”, fresh martensite as “FM”, and retained austenite as “γR”.

[0277] Area ratio of tempered martensite, bainite, and fresh martensite

[0278] After etching the observation surface of the observation sample using Nital, 10 fields of view were observed at a magnification of 2000x using a scanning electron microscope (SEM) to obtain SEM images.

[0279] For the obtained SEM images, the area percentage (unit: %) of each tissue was calculated. The average area percentage of 10 fields of view was taken as the area percentage of each tissue.

[0280] In the SEM image, the light gray area was determined to be fresh martensite, and the dark gray area where carbides were precipitated was determined to be tempered martensite and bainite.

[0281] Since fresh martensite and retained austenite cannot be clearly distinguished in SEM images, the area ratio of fresh martensite was set as the value obtained by subtracting the area ratio of retained austenite obtained by the method described below from the area ratio of the light gray region.

[0282] Area percentage of retained austenite

[0283] The area percentage of retained austenite (unit: %) was determined by X-ray diffraction.

[0284] Specifically, first, the observation surface of the observation sample was polished 0.1 mm in the plate thickness direction, and also polished 0.1 mm by chemical polishing to obtain a polished surface.

[0285] For this polished surface, using CoKα lines, the integrated intensity of the diffraction peaks of each plane of {200}, {220}, and {311} of fcc iron, and each plane of {200}, {211}, and {220} of bcc iron was measured.

[0286] Next, the ratio (integral intensity) of the integral intensity of each face of fcc iron {200}, {220}, and {311} to the integral intensity of each face of bcc iron {200}, {211}, and {220} was calculated.

[0287] The average value of the nine calculated integrated strength ratios was taken as the volume fraction of the retained austenite, and this volume fraction was considered as the area fraction of the retained austenite (unit: %).

[0288] Average particle size of precipitate A, N S and N L 》

[0289] A replica sample was collected from the observation surface of the observed sample using the replica method.

[0290] For the collected replica sample, a transmission electron microscope (TEM) was used to observe 10 fields of view at a magnification of 20,000x with an acceleration voltage of 200 kV, and TEM images were obtained. The size of one field of view was set to 0.5 μm × 0.5 μm.

[0291] The presence of precipitates was confirmed by observing the obtained TEM images.

[0292] In addition, energy dispersive X-ray spectroscopy (EDS) with the same field of view as the TEM image was performed to identify the elements contained in the precipitate.

[0293] Among the precipitates confirmed in TEM, a precipitate containing at least one selected from the group consisting of Ti, Nb, and V was identified as precipitate A.

[0294] The circular equivalent diameter of each precipitate identified as precipitate A was determined, and the average value over 10 viewing hours was taken as the average particle size of precipitate A (unit: μm).

[0295] In addition, the major axis of precipitate A was measured.

[0296] Specifically, for each particle of precipitate identified as precipitate A, the longest length passing through the particle was measured and this was taken as the major axis of precipitate A.

[0297] Next, precipitate A with a major axis of 0.050 μm or less (i.e., precipitate A S By measuring the number of ) and dividing the measured number by the area of ​​10 fields, precipitate A S Number density N S (Unit: pieces / ㎛) 2 ) saved.

[0298] Likewise, precipitate A with a major axis greater than 0.050 μm (i.e., precipitate A L By measuring the number of ) and dividing the measured number by the area of ​​10 fields, precipitate A LNumber density N L (Unit: pieces / ㎛) 2 ) saved.

[0299] Also, N S and N L The ratio of (N S / N L ) saved.

[0300] <Measurement of diffusible hydrogen content in the river>

[0301] A test specimen of size 5 mm × 30 mm was cut from the obtained steel plate. If a plating layer (zinc plating layer or alloyed zinc plating layer) was formed, the plating layer was removed using a router (precision grinder).

[0302] The test specimen was placed inside a quartz tube, and the inside of the quartz tube was replaced with argon gas (Ar). After that, the inside of the quartz tube was heated to 400 ℃ at a rate of 200 ℃ / hr, and the amount of hydrogen generated from the inside of the quartz tube during the heating was measured by a heating analysis method using a gas chromatograph.

[0303] The cumulative value of the amount of hydrogen detected in the temperature range from room temperature (25 ℃) to less than 250 ℃ was calculated as the amount of diffusible hydrogen in steel (unit: mass%). The results are shown in Table 3 below.

[0304] <Evaluation>

[0305] The obtained steel plates were evaluated by the following tests. The results are shown in Table 3 below.

[0306] 《Tensile Test》

[0307] From the obtained steel plate, a JIS No. 5 test specimen was taken with the direction perpendicular to the rolling direction as the tensile direction. Using the taken test specimen, a tensile test was performed in accordance with JIS Z 2241 (2011), and the tensile strength (TS) and elongation (EL) were measured.

[0308] If TS is 1320 MPa or higher, it was evaluated as high strength.

[0309] If EL is 10.0% or higher, it was evaluated as having excellent ductility.

[0310] Hole Expansion Test

[0311] For the obtained steel plate, a hole expansion test was performed in accordance with JIS Z 2256 (2010).

[0312] Specifically, the obtained steel plate was cut to obtain a test specimen of 100 mm × 100 mm size. A hole with a diameter of 10 mm was punched in the obtained test specimen with a clearance of 12 ± 1 %. Subsequently, using a die with an inner diameter of 75 mm, a conical punch with an apex angle of 60° was inserted into the hole while applying a creasing force of 9 ton, and the hole diameter D at the crack initiation limit f [mm] was measured. The initial hole diameter was set to D0 (unit: mm), and the hole expansion rate λ (unit: %) was calculated from the following formula. If λ is 25% or more, the hole expandability was evaluated as excellent.

[0313] λ = {(D f -D0) / D0}×100

[0314] Evaluation Test for Delayed Fracture Characteristics

[0315] Test specimens were taken from the obtained steel plate. If a plating layer was formed, it was dissolved and removed using diluted hydrochloric acid, and after storing at room temperature for 1 day (dehydrogenation treatment), test specimens were taken.

[0316] The size of the test specimen was set so that the length of the long side (length in the direction perpendicular to rolling) was 100 mm and the length of the short side (length in the rolling direction) was 30 mm.

[0317] In the test specimen, the cross-section on the long side was designated as the evaluation cross-section, and the cross-section on the short side was designated as the non-evaluation cross-section.

[0318] The cutting of the evaluation cross-section was performed by shearing. The clearance for shearing was 10%, and the rake angle was 0.5 degrees. The evaluation cross-section was left in the sheared state; that is, no machining was performed to remove the burrs. On the other hand, for the non-evaluation cross-section, machining was performed to remove the burrs.

[0319] Bending was performed on these test specimens. The bending was performed under conditions where the ratio of the bending radius R to the plate thickness t of the test specimen (R / t) was 4.0 and the bending angle was 90 degrees (V-bending).

[0320] For example, when the plate thickness t is 2.0 mm, a punch with a tip radius of 8.0 mm was used. More specifically, a punch having the tip radius described above and also having a U-shape (the tip part is semicircular and the thickness of the body part is 2R) was used.

[0321] In addition, for the bending process, a die with a corner bending radius of 30 mm was used.

[0322] In the bending process, a bending portion with a bending angle of 90 degrees was formed on the test specimen by adjusting the depth to which the punch pushes the test specimen.

[0323] A test specimen with a formed bending section was placed between and tightened using a hydraulic jack, and bolted while the following residual stresses S1, S2, or S3 were applied to the outermost layer of the bending section.

[0324] · Residual stress S1: Residual stress between 1300 MPa and 1500 MPa

[0325] · Residual stress S2: Residual stress exceeding 1500 MPa and not exceeding 1700 MPa

[0326] · Residual stress S3: Residual stress exceeding 1,700 MPa and not exceeding 1,900 MPa

[0327] For each applied residual stress S1, S2, and S3, the number of test specimens was set to 2.

[0328] The required tightening amount was calculated by CAE (Computer Aided Engineering) analysis.

[0329] Bolt tightening was performed by passing the bolt through an elliptical hole (short axis: 10 mm, long axis: 15 mm) formed 10 mm inward from the non-standard cross-section of the test specimen.

[0330] The test specimens after bolt tightening were immersed in hydrochloric acid (aqueous hydrogen chloride solution) with a pH of 4, and the pH was maintained constant at 25°C. The amount of hydrochloric acid was set to at least 1 L per test specimen.

[0331] After 48 hours had elapsed following immersion, the presence or absence of microcracks visible to the naked eye (having a length of approximately 1 mm) was checked on the test specimens in hydrochloric acid. These microcracks indicate the initial state of delayed fracture.

[0332] The results based on the presence or absence of microcracks ("×", "△", "○", or "◎" shown below) are listed in Table 3 below.

[0333] × : In the test specimen subjected to residual stress S1, one or more microcracks were identified.

[0334] △ : In the specimen with residual stress S1, no microcracks were detected, but in the specimen with residual stress S2, one or more microcracks were detected.

[0335] ○ : In the test specimens loaded with residual stress S1 and residual stress S2, no microcracks were detected, but in the test specimen loaded with residual stress S3, one or more microcracks were detected.

[0336] ◎ : No microcracks were detected in any of the test specimens.

[0337] If it is "△", "○", or "◎", it was evaluated as having excellent delayed breakdown characteristics.

[0338] "○" or "◎" is preferable because it has superior delayed fracture resistance, and "◎" is more preferable because it has even superior delayed fracture resistance.

[0339] The lines in Tables 1 to 3 below indicate areas outside the scope of the present invention.

[0340]

[0341]

[0342]

[0343] <Summary of Evaluation Results>

[0344] As shown in Table 3 above, the steel plates of No. 1, 3 to 5, 8 to 9, 11 to 13, 15 to 17, 21 to 22, 26, 30 to 31 and 39 had at least one of the tensile strength, ductility, hole expansion, and delayed fracture resistance characteristics insufficient.

[0345] In this regard, it was found that the steel plates No. 2, 6 to 7, 10, 14, 18 to 20, 23 to 25, 27 to 29, 32 to 38, and 40 to 45 all had a tensile strength of 1320 MPa or higher, and also had excellent ductility, hole expansion, and delayed fracture resistance.

[0346] Among these steel plates, the steel plate satisfying all of the following (i) to (v) had an evaluation result of “◎” for delayed fracture characteristics.

[0347] (i) Area percentage of retained austenite: 12.0% or less

[0348] (ii) Average particle size of precipitate A: 0.020 μm or less

[0349] (iii) N S : 310 pieces / ㎛ 2more

[0350] (iv) N S / N L : 13.0 or higher

[0351] (v) Diffusible hydrogen content in steel: 0.25 mass ppm or less

[0352] For steel plates that do not satisfy at least one of the above (i) to (v), the evaluation result of the delayed fracture characteristic was “○”.

[0353] In addition, the steel plate of No. 44 (steel symbol: T) satisfies all of the above (i) to (v), but because the amount of C is slightly lower, it is presumed that the evaluation result of the delayed fracture characteristic was “○”.

[0354] N S / N L For steel plates in which the value is 12.1 or less, or the average particle size of precipitate A is 0.040 μm or more, the evaluation result of the delayed fracture resistance was “△”.

Claims

Claim 1 A steel having a composition in mass% comprising C: 0.130–0.350%, Si: 0.50–2.50%, Mn: 2.00–4.00%, P: 0.100% or less, S: 0.0500% or less, Al: 0.010–2.000%, N: 0.0100% or less, and at least one element selected from the group consisting of Ti: 0.001–0.100%, Nb: 0.001–0.100%, and V: 0.001–0.500%, with the remainder being Fe and unavoidable impurities, and having a microstructure, wherein the diffusible hydrogen content in the steel is 0.50 mass ppm or less, and wherein the microstructure comprises tempered martensite and bainite Precipitate A having a total area ratio of 70.0 to 95.0%, an area ratio of fresh martensite of 15.0% or less, an area ratio of retained austenite of 5.0 to 15.0%, an average grain size of precipitate A, which is a carbide, nitride, or carbonitride containing at least one element selected from the group consisting of Ti, Nb, and V, and has a major axis of 0.055 μm or less. S Number density N S 10 pieces / ㎛ 2 That is all, and the above precipitate A S Number density N S Wow, precipitate A, which is the above-mentioned precipitate A with a major axis greater than 0.050 μm. L Number density N L Of N S / N L High-strength steel plate with a value of 10.0 or higher. Claim 2 A high-strength steel sheet according to claim 1, wherein the composition of the above components further comprises, in mass%, at least one element selected from the group consisting of W: 0.500% or less, B: 0.0100% or less, Ni: 2.000% or less, Co: 2.000% or less, Cr: 1.000% or less, Mo: 1.000% or less, Cu: 1.000% or less, Sn: 0.500% or less, Sb: 0.500% or less, Ta: 0.100% or less, Zr: 0.200% or less, Hf: 0.020% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, and REM: 0.0100% or less. Claim 3 A high-strength steel sheet having a plating layer on its surface, according to claim 1 or 2. Claim 4 In claim 3, the high-strength steel sheet wherein the plating layer is an alloyed plating layer. Claim 5 A method for manufacturing a high-strength steel sheet as described in claim 1 or 2, wherein a steel slab having the compositional component described in claim 1 or 2 is heated to 1100°C or higher and hot-rolled at a finishing rolling end temperature of 850 to 950°C to obtain a hot-rolled steel sheet, the hot-rolled steel sheet is coiled at a coiling temperature T of 400 to 700°C, held therein, and subsequently cold-rolled to obtain a cold-rolled steel sheet, and a heat treatment is performed on the cold-rolled steel sheet, wherein in the said holding, the sum of the times during which the temperature of the coiled hot-rolled steel sheet is at least the coiling temperature T - 50°C is denoted by the unit s and t satisfies the following Equation 1, and in the said heat treatment, the cold-rolled steel sheet is maintained at a temperature range T1 of 800 to 950°C for 30 seconds or more, and thereafter at 150 to 250°C A method for manufacturing a high-strength steel sheet, wherein the steel sheet is cooled to a cooling stop temperature T2, and then maintained at a temperature range T3 of 250 to 400 ℃ for at least 30 seconds. Formula 1: 0.001 < [1.17 × 10⁻⁶ -6 ×{t / (T+273.15)}] 1 / 3 < 0.050 Claim 6 A method for manufacturing a high-strength steel plate according to claim 5, wherein, prior to hot rolling, the steel slab is cast and then cooled, and in the cooling of the steel slab, the average cooling rate v1 at 700 to 600 ℃ is 5.0 ℃ / h or higher, and the average cooling rate v2 at 600 to 500 ℃ is 2.5 ℃ / h or higher. Claim 7 A method for manufacturing a high-strength steel sheet according to claim 5, wherein, after the heat treatment, a plating treatment is performed on the cold-rolled steel sheet to form a plating layer. Claim 8 A method for manufacturing a high-strength steel sheet according to claim 6, wherein, after the heat treatment, a plating treatment is performed on the cold-rolled steel sheet to form a plating layer. Claim 9 A method for manufacturing a high-strength steel sheet according to claim 7, wherein the plating treatment comprises an alloying plating treatment that alloys the plating layer. Claim 10 A method for manufacturing a high-strength steel sheet according to claim 8, wherein the plating treatment comprises an alloying plating treatment that alloys the plating layer.

Citation Information

Patent Citations

  • High-strength steel sheet and method for manufacturing same

    WO2021019947A1